2018
DOI: 10.17140/emoj-4-151
|View full text |Cite
|
Sign up to set email alerts
|

Long Working Hour Related Medical Errors and Patient Outcomes among Physicians: A Systematic Review

Abstract: Inspired by the famous Libby Zion case in 1984, which revealed the underlying flaw in the medical system at the time──the exploitation of junior medical staff and the inadequate surveillanceby attending physicians, authors of this systemic review aim to investigate the potential consequence of overworking in medical scenarios. Methods Excerpta medica database (EMBASE) and PubMed had been systematically searched, bibliographies of relevant studies additionally reviewed. Four cohorts and three randomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…In the study conducted by Filiz [19] on healthcare workers, it was found that long working hours reduced the patient safety attitudes of the employees. Similar to the results of all these studies, it has been observed in the literature that there are many different studies stating that the increase in weekly working hours increases the possibility of encountering errors or adverse events that threaten patient safety [20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 55%
“…In the study conducted by Filiz [19] on healthcare workers, it was found that long working hours reduced the patient safety attitudes of the employees. Similar to the results of all these studies, it has been observed in the literature that there are many different studies stating that the increase in weekly working hours increases the possibility of encountering errors or adverse events that threaten patient safety [20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 55%